Assessment of Proximal Tubular Function by Tubular Maximum Phosphate Reabsorption Capacity in Heart Failure. Issue 2 (February 2022) - Emmens, Johanna E.; de Borst, Martin H.; Boorsma, Eva M.; Damman, Kevin; Navis, Gerjan; van Veldhuisen, Dirk J.; Dickstein, Kenneth; Anker, Stefan D.; Lang, Chim C.; Filippatos, Gerasimos; Metra, Marco; Samani, Nilesh J.; et al.
Visual Abstract: Abstract : Background and objectives: The estimated glomerular filtration rate (eGFR) is a crucial parameter in heart failure. Much less is known about the importance of tubular function. We addressed the effect of tubular maximum phosphate reabsorption capacity (TmP/GFR), a parameter of proximal tubular function, in patients with heart failure. Design, setting, participants, & measurements: We established TmP/GFR (Bijvoet formula) in 2085 patients with heart failure and studied its association with deterioration of kidney function (>25% eGFR decrease from baseline) and plasma neutrophil gelatinase–associated lipocalin (NGAL) doubling (baseline to 9 months) using logistic regression analysis and clinical outcomes using Cox proportional hazards regression. Additionally, we evaluated the effect of sodium-glucose transport protein 2 (SGLT2) inhibition by empagliflozin on tubular maximum phosphate reabsorption capacity in 78 patients with acute heart failure using analysis of covariance. Results: Low TmP/GFR (<0.80 mmol/L) was observed in 1392 (67%) and 21 (27%) patients. Patients with lower TmP/GFR had more advanced heart failure, lower eGFR, and higher levels of tubular damage markers. The main determinant of lower TmP/GFR was higher fractional excretion of urea ( P <0.001). Lower TmP/GFR was independently associated with higher risk of plasma NGAL doubling (odds ratio, 2.20; 95% confidence interval, 1.05 to 4.66; P =0.04) but not with deterioration of kidney function. Lower TmP/GFR was associated with higher risk of all-cause mortality (hazard ratio, 2.80; 95% confidence interval, 1.37 to 5.73; P =0.005), heart failure hospitalization (hazard ratio, 2.29; 95% confidence interval, 1.08 to 4.88; P =0.03), and their combination (hazard ratio, 1.89; 95% confidence interval, 1.07 to 3.36; P =0.03) after multivariable adjustment. Empagliflozin significantly increased TmP/GFR compared with placebo after 1 day ( P =0.004) but not after adjustment for eGFR change. Conclusions: TmP/GFR, a measure of proximal tubular function, is frequently reduced in heart failure, especially in patients with more advanced heart failure. Lower TmP/GFR is furthermore associated with future risk of plasma NGAL doubling and worse clinical outcomes, independent of glomerular function.